SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN MUTASI TUGAS PADA KANTOR KEPOLISIAN POLDA SUMUT MENGGUNAKAN METODE MULTI ATTRIBUTE UTILITY THEORY - Nuraisana Nuraisana (Jurnal Mantik Penusa, 2019)
At each agency or organization the police often carry out a series of placement or transfer activities. Mutations in a company or organization are carried out in particular interests of the company or its individuals. In this case, there are many members of the police who submit mutations so that the police have difficulty in determining which members are eligible to be transferred. Currently the development of technology is very rapid, computers are used not only as data processing but also as a solution to solve problems in various fields of science, one of which is a decision support system. Decision support systems have added value in assisting decision making by utilizing data and models to solve unstructured problems. In this case the decision support system is used to determine the mutation of tasks at the North Sumatra Regional Police office using the Multi Attribute Utility Theory method. The Multi Attribute Utility Theory is used to find the weighted sum of the performance ratings for each alternative based on the value of each criterion. Ranking is the final result of the calculation of the Multi Attribute Utility Theory method which determines whether or not a member of the Police will be transferred.